Jacobitism and cultural memory, 1688-1830 - Davis, Leith, 1960- (Cambridge elements. Elements in eighteenth-century connections, 2025)
This Element has three objectives. First, it highlights the diversity of the nature of Jacobitism in the long eighteenth century by drawing attention to multi-media representations of Jacobitism and also to multi-lingual productions of the Jacobites themselves, including works in Irish Gaelic, Latin, Scots, Scots Gaelic and Welsh. Second, it puts the theoretical perspectives of cultural memory studies and book history in dialogue with each other to examine the process through which specific representations of the Jacobites came to dominate both academic and popular discourse. Finally, it contributes to literary studies by bringing the literature of the Jacobites and Jacobite Studies into the purview of more mainstream scholarship on eighteenth- and nineteenth-century literatures, providing a fuller perspective on the cultural landscape of that period and correcting a tendency to ignore or downplay the presence of Jacobitism. This title is also available as Gold Open Access on Cambridge Core.